INVESTIGATING THE FEASIBILITY OF USING RECYCLED FIBRES INSTEAD OF INDUSTRIAL FIBRES IN SHOTCRETE - Shahla Miri Darmarani; Erfan Khoshzaher; Hamid Chakeri; Rahman Mirzaei (Rudarsko-geološko-naftni Zbornik)
Shotcrete is one of the standard systems used in the tunnelling industry, including cement, sand, water, and additives. Adding fibres to shotcrete is a method to enhance its mechanical properties. This study is laboratory research investigating the feasibility of using recycled steel fibres instead of industrial fibres and the effect of adding industrial and recycled fibres on the mechanical properties of shotcrete. For this research, laboratory samples were created using industrial steel fibres and recycled steel fibre types 1 and 2 sourced from worn tires. Laboratory samples include cubic and cylindrical samples with 12 mixing designs. These 12 mixing designs are plain shotcrete, shotcrete containing 1, 2, and 5 percent industrial steel fibres, shotcrete containing 0.5, 1, 1.5, and 2 percent type 1 recycled fibre, and shotcrete containing 0.5, 1, 1.5, 2 percent type 2 recycled fibres. Laboratory tests include compressive strength, tensile strength, and modulus of elasticity for durations of 3, 7, and 28 days. According to the results, adding industrial and recycled fibres to the shotcrete composition improves the resistance properties of shotcrete, and recycled fibres can replace industrial fibres.